Leukocytes Differentiation of Oreochromis niloticus Fed with Herbs Fermented and Challenged with Aeromonas hydrophila - Putri, Annisa Dwi; Riauwaty, Morina; Syawal, Henni (Jurnal Akuakultur SEBATIN, 2024)
Herb-fermented medicine consists of Curcuma zanthorrhiza, Curcuma domestica Val. and Kaempferia galanga, which contains active substances to overcome disease. This research was conducted from August to December 2021 at the Marine Science Biotechnology Laboratory and Fish Parasite and Disease Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The method used in this study was an experiment using a Complete Randomized Design (CRD), one factor with five treatments and three replications. The treatment of this study was Kn: Negative control (feeding without herbs fermented and without being challenged Aeromonas hydrophila), Kp: Positive Control (feeding without herbs fermented and challenged with A. hydrophila), P1; P2 and P3: Fed herbs fermented at a dose of 150, 175 and 200 mL/kg and challenged with A. hydrophila. The fish used was 6-7 BW with a 1 fish/4L density. The result showed the best dose was in P3, with a total of leukocytes 5,01x104 cells/mm3, Lymphocytes 77,67%, Neutrophils 7,67%, Monocytes 14,67%, Phagocytic activity 37,67%. Based on the data obtained, it can be concluded that fermented herbs have a significant effect on the leukocyte differentiation of Oreochromis niloticus